2005
DOI: 10.1111/j.1365-2249.2005.02941.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of paramyosin T cell epitopes associated with human resistance toSchistosoma mansonireinfection

Abstract: SummaryParamyosin, a Schistosoma mansoni myoprotein associated with human resistance to infection and reinfection, is a candidate antigen to compose a subunit vaccine against schistosomiasis. In this study, 11 paramyosin peptides selected by TEPITOPE algorithm as promiscuous epitopes were produced synthetically and tested in proliferation and in vitro human leucocyte antigen (HLA)-DR binding assays. A differential proliferative response was observed in individuals resistant to reinfection compared to individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
0
17
0
2
Order By: Relevance
“…[64]. This, including the positive antibody binding of very small amounts of microfilarial and adult native paramyosin detected herein, suggests that Ol -PARA should be tested as a potential vaccine candidate.…”
Section: Discussionmentioning
confidence: 57%
“…[64]. This, including the positive antibody binding of very small amounts of microfilarial and adult native paramyosin detected herein, suggests that Ol -PARA should be tested as a potential vaccine candidate.…”
Section: Discussionmentioning
confidence: 57%
“…Pooled odds ratio showed that although there was a positive association of male gender and reinfection with schistosomes, the association was only slightly statistically significant (OR = 1.45, 95% CI = 1.02–2.05, Z = 2.09, p  = 0.04). Sensitivity analysis by subgroup analysis based on the species studied showed that statistically significant positive association was observed for association of male gender with reinfection with S. mansoni ( p  = 0.02) [25], [28]–[32], [43][45] and S. japonicum ( p  = 0.002) [24], [42], [46], while the association for reinfection with S. haematobium [26], [34][36], [39], [40] was not statistically significant ( p  = 0.30) (Figure 3). The exclusion of S. mansoni or S. japonicum subgroups in the meta-analysis yielded effect measures which were not statistically significant ( p  = 0.22 and p  = 0.23, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Epitope prediction was carried out as described previously [52][53][54]. Briefly, the amino acid sequences of SjHSP60 (GenBank accession no.…”
Section: Prediction Of Epitopes and Synthesis Of Peptidesmentioning
confidence: 99%